ANALISIS DATA SISTEM RUJUKAN TERINTEGRASI (SISRUTE) DI INSTALASI GAWAT DARURAT (IGD) INFEKSI RSUP DR. SARDJITO - Ni Kadek Ari Astiti; Happy Indah Kusumawati; Sutono (Journal of Health Service Management, 2023)
Background: The health referral system regulates the delegation of duties and responsibilities of health services in reverse. SISRUTE (Integrated Referral Information System) as a reference for managing national referrals in Indonesia. During the pandemic, most hospitals were overwhelmed with patients; therefore, hospitals were encouraged to optimize the use of SISRUTE. Objective:This study aims to identify the implementation of SIS-RUTE in the Infectious Emergency Room of RSUP Dr Sardjito.Method:This research used quantitative descriptive research witha retrospective approach. The sample of this study was secondarydata in the SISRUTE application from June-August 2021. This study used a total sampling technique. The instrument used worksheets,and data analysis was performed using a univariate method to findout reasons for referrals rejected, reasons for referrals received, and SISRUTE response time.Result:Referral patients with Social Security Agency for Health(BPJS) were (42%). Most referrals came from Type C Hospital(41.29%) during the afternoon shift (36.8%). The highest reason forrefusing referrals was limited room (68.03%). The most needed wasthe Intensive Care Unit (ICU) (52.68%). The highest SISRUTE re-sponse time was in the range of 1-5 minutes (59.73%).Conclusion:The implementation of SISRUTE in the IGD InfectionRSUP Dr. Sardjito Yogyakarta is generally good, with a fast responsetime. Referrals are mostly accepted due to the availability of inpatientrooms. The reasons for referrals rejected are due to the limited ICUspace.